2022
DOI: 10.3390/cells11111768
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-CGRP Antibody Fremanezumab Lowers CGRP Release from Rat Dura Mater and Meningeal Blood Flow

Abstract: Monoclonal antibodies directed against the neuropeptide calcitonin gene-related peptide (CGRP) belong to a new generation of therapeutics that are effective in the prevention of migraine. CGRP, a potent vasodilator, is strongly implicated in the pathophysiology of migraine, but its role remains to be fully elucidated. The hemisected rat head preparation and laser Doppler flowmetry were used to examine the effects on CGRP release from the dura mater and meningeal blood flow of the subcutaneously injected anti-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 94 publications
2
23
0
Order By: Relevance
“…Regarding the clinical studies of CGRP, many data remain unavailable, including data on interictal M0, MA, CM, and central NP. Hopefully, more clinical studies will reveal the consequences of CGRP modulator administration to clarify its efficacy in those subtypes of pain disorders [ 222 , 223 , 224 , 225 , 226 ]. Different TRP ion channels play distinct roles in both migraine and NP [ 227 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the clinical studies of CGRP, many data remain unavailable, including data on interictal M0, MA, CM, and central NP. Hopefully, more clinical studies will reveal the consequences of CGRP modulator administration to clarify its efficacy in those subtypes of pain disorders [ 222 , 223 , 224 , 225 , 226 ]. Different TRP ion channels play distinct roles in both migraine and NP [ 227 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 CGRP, generally considered a neurotransmitter, does not evoke pain directly but acts on the trigeminal system to regulate activities of vascular endothelial cells, immune-inflammatory cells, neurons, and glial cells, thus initiating and maintaining both peripheral and central sensitization (Figure 1). [19][20][21] Abundant experiments have shown that CGRP is crucial in promoting orofacial pain. In an experimental model of orthodontic pain, periodontal injection of CGRP increased the expression of CGRP in periodontal tissues and aggravated orofacial pain, while administration of CGRP receptor antagonists had the opposite effect, 4 suggesting that periodontal CGRP might participate in positive feedback aiming to amplify orofacial pain signals.…”
Section: Calcitonin Gene-related Peptide Cgrpmentioning
confidence: 99%
“…CGRP mainly mediate prolonged vasodilation and increased blood flow through endotheliumdependent and NO-dependent pathway, which can not only increase NO and make peripheral trigeminal afferent fibres hyperalgesia but also promotes the aggregation of inflammatory mediators and inflammatory cell, thereby exacerbating local inflammation. 19 Besides vascular effect, CGRP promoted neurogenic inflammation and subsequent peripheral sensitization by acting directly on local immune inflammatory cells, prompting the release of various inflammatory mediators and cytokines. 23 Some of these substances can induce phosphorylation of transient receptor potential vanilloid subfamily member 1 (TRPV1), the transient receptor potential ankyrin 1 ion channel (TRPA1), or voltage-gated sodium channels (VGSCs), triggering action potentials and thereby activating nociceptors, while others could lead to peripheral sensitization and hyperalgesia by reducing the activation threshold of peripheral nociceptors and increasing neuronal responses to stimuli.…”
Section: Calcitonin Gene-related Peptide Cgrpmentioning
confidence: 99%
“…The exocytosis of the CGRP determines three main phenomena. The first one is vasodilation at the meningeal level, as unequivocally demonstrated by an experiment with CGRP-blocking antibodies in rats [ 26 ]. Furthermore, the action of CGRP on pericytes at the endothelial levels determines an increase in the permeability of meningeal arteries [ 27 ].…”
Section: Current Understanding Of Migraine Pathophysiology With Relev...mentioning
confidence: 99%